2008
DOI: 10.6090/jarq.42.79
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological Analysis on Effect of Planting Pattern on Biomass Production and Grain Yield in Rice

Abstract: Increasing the biomass productivity of rice is a critical research target for improving the yield potential. This paper reviews ecophysiological studies on biomass production as affected by agronomic techniques and cultivars. In addition, we examined the effects of the planting pattern on the biomass production using cv. Takanari, a high-yielding and lodging resistant cultivar. The results showed that greater biomass production and grain yield were observed in plants with the combination of one plant per hill,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Two indigenous varieties Moulata and Lalmota had identical but significantly larger number of tillers per m 2 compared with two HYVs and one indigenous variety Sadamota. Rice grain yield is positively and linearly related with the number of tillers per unit area [9,10]. Wang et al [11] suggested selection of genotypes with tillering capacity for obtaining higher yield in rice.…”
Section: Morphological Charactersmentioning
confidence: 99%
“…Two indigenous varieties Moulata and Lalmota had identical but significantly larger number of tillers per m 2 compared with two HYVs and one indigenous variety Sadamota. Rice grain yield is positively and linearly related with the number of tillers per unit area [9,10]. Wang et al [11] suggested selection of genotypes with tillering capacity for obtaining higher yield in rice.…”
Section: Morphological Charactersmentioning
confidence: 99%
“…Huang et al (2018) investigated machine‐transplanted double cropping rice and found that increasing hill density can compensate for yield loss from reduced N input. An increase in crop yield under dense planting was reported as a consequence of the rise in biomass (Katsura et al, 2010; San‐Oh et al, 2008), which might be attributed to the greater potential capacity of the crop canopy to capture solar radiation, water, and nutrients in the deep soil layer (Dingkuhn et al, 2015; Du et al, 2015). For example, increased leaf area index (LAI) and an effective blade spatial arrangement ensure that plant photosynthesis meets the needs of high yield (Yoshida, 1981).…”
mentioning
confidence: 99%
“…Thus, we conclude that the leaf inclination angle is a major determinant of the O 3 inhibition in our case. In paddy field conditions, however, individual rice plants are affected by mutual shading during growth and receive considerably different incident light within the canopy (San-oh et al, 2008). Furthermore, the profile of canopy O 3 concentration may be complex.…”
Section: Discussionmentioning
confidence: 99%